The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jfb.13056
|View full text |Cite
|
Sign up to set email alerts
|

Tidal amplitude and fish abundance in the mouth region of a small estuary

Abstract: Using an acoustic underwater camera (Dual Frequency IDentification SONar, DIDSON), the abundance and direction of movement of fishes > 80 mm total length (LT ) in the mouth of a small South African estuary during spring and neap tidal cycles were observed. While the sizes of fishes recorded were consistent across both tide cycles, the number of fishes passing the camera was significantly greater during the smaller neap tides. Schooling behaviour was more pronounced for fishes that were travelling into the estu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Although automatic analysis techniques have improved, manual processing is still the usual method to count and measure fish with DIDSON cameras within the scope of fish monitoring scientific surveys (Becker et al ., ; Crossman et al ., ; Doehring et al ., ; Lilja et al ., ; Ogburn et al ., ; Viehman & Zydlewski, ), but also in uses by different kinds of operators (for instance fish farmers, stakeholders, consultants, operators of once‐off surveys, etc .). Burwen et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although automatic analysis techniques have improved, manual processing is still the usual method to count and measure fish with DIDSON cameras within the scope of fish monitoring scientific surveys (Becker et al ., ; Crossman et al ., ; Doehring et al ., ; Lilja et al ., ; Ogburn et al ., ; Viehman & Zydlewski, ), but also in uses by different kinds of operators (for instance fish farmers, stakeholders, consultants, operators of once‐off surveys, etc .). Burwen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although automatic analysis techniques have improved, manual processing is still the usual method to count and measure fish with DIDSON cameras within the scope of fish monitoring scientific surveys (Becker et al, 2016;Crossman et al, 2011;Doehring et al, 2011;Lilja et al, 2010;Ogburn et al, 2017;Viehman & Zydlewski, 2015), but also in uses by different kinds of operators (for instance fish farmers, stakeholders, consultants, operators of once-off surveys, etc.). Burwen et al (2007Burwen et al ( , 2010 found a strong linear relationship (r 2 = 0.9) between manual DIDSON-based lengths and true lengths for a variable number of swimming fish at different ranges (i.e., distance to the camera).…”
Section: Introductionmentioning
confidence: 99%
“…High counting accuracy is often achieved due to the high‐quality data obtained and the single swimming direction of migrating fishes. In addition, MFLS is also widely used in surveys of habitats, such as artificial reefs (Guo et al, 2018; Plumlee et al, 2020), estuary (Becker et al, 2016; Becker et al, 2017; Lankowicz et al, 2020), river (Hayes et al, 2015; Kerschbaumer et al, 2020; Mora et al, 2015), lake (Jing, Han, Wang, et al, 2018a), estuarine shoreline (Smith et al, 2021), offshore habitat (Artero et al, 2021; Tassetti et al, 2020; Van Hal et al, 2017), reservoir (Huang & Gong, 2020; Mo et al, 2015; Shen et al, 2018), etc., to study the fish stock and interaction of fishes with the habitats. The fish density is typically calculated to estimate abundance and studied for the habitat population distribution (Plumlee et al, 2020; Zhou et al, 2014).…”
Section: Applications In Fish Monitoringmentioning
confidence: 99%
“…Fisheries scientists have used acoustic cameras to monitor fish (and other animals) by detecting their direct acoustic image and/or their acoustic shadow (Horne 2000;Trenkel et al 2011;Martignac et al 2015). For example, acoustic cameras have been used in saltmarsh habitats to analyse predator-prey interactions (Boswell et al 2019) and fish movement in tidal passageways (Kimball et al 2010;Bennett et al 2020); in areas of high turbidity caused by sedimentation to estimate size and abundance of key demersal fish (Artero et al 2021); and, in intermittently closed estuaries to determine the abundance and the direction of fish movement, and the distribution of different sized fish (Becker et al 2016(Becker et al , 2017. Coupling of direct acoustic images and acoustic shadows has enabled identification of different species (Able et al 2014;Artero et al 2021).…”
Section: Introductionmentioning
confidence: 99%